Meningeal SWI/SNF related, matrix‐associated, actin‐dependent regulator of chromatin, subfamily B member 1 (SMARCB1)‐deficient tumours: an emerging group of meningeal tumours. (28th December 2016) - Dadone, B.; Fontaine, D.; Mondot, L.; Cristofari, G.; Jouvet, A.; Godfraind, C.; Varlet, P.; Ranchère‐Vince, D.; Coindre, J.‐M.; Gastaud, L.; Baudoin, C.; Peyron, A.‐C.; et al.
Abstract : Aims: Bi‐allelic inactivation of SWI/SNF related, matrix‐associated, actin‐dependent regulator of chromatin, subfamily B member 1 (SMARCB1; also known as INI1) and loss of immunohistochemical expression of SMARCB1 define the group of SMARCB1‐deficient tumours. Initially highlighted in malignant rhabdoid tumours, this inactivation has subsequently been observed in several intra and extracranial tumours. To date, primary meningeal SMARCB1‐deficient tumours have not been described. We report two cases of meningeal SMARCB1‐deficient tumours occurring in adults. Methods: We performed immunohistochemical analyses, comparative genomic hybridization, fluorescence in situ hybridization and targeted next‐generation sequencing. Results: The first meningeal tumour was a solitary mass, composed of rhabdoid, adenoid, chordoid and sarcomatoid areas. The second case presented as multiple, bilateral, supra and infratentorial nodules, was composed of fusiform and ovoid cells embedded in a myxoid stroma. Tumour cells were positive for epithelial membrane antigen (EMA), vimentin and CD34 and negative for SMARCB1 and meningothelial, melanocytic, muscular, glial markers. In the first case, one allele of SMARCB1 was completely deleted, whereas in the second case, loss of expression of SMARCB1 was observed as a consequence of a homozygous deletion of SMARCB1 . Conclusions: The phenotype and genotype of these two cases did not fit diagnostically with entities already known to be SMARCB1‐deficient tumours. As both tumours shared common features, they are regarded as belonging to an emerging group of primary meningeal SMARCB1‐deficient tumours, not described to date. To facilitate the identification and characterization of these tumours, we recommend SMARCB1 immunohistochemistry for primary meningeal tumours which are difficult to classify, especially if immunopositive for EMA and CD34. Abstract : This newly described group of primary meningeal SMARCB1‐deficient tumours expands our understanding of difficult to classify primary meningeal tumours.